2005
DOI: 10.1080/00365520510023305
|View full text |Cite
|
Sign up to set email alerts
|

Skip inflammation of the appendiceal orifice: A prospective endoscopic study

Abstract: Discontinuous inflammation of the appendiceal orifice is common in patients with IBD irrespective of clinical activity. However, patients with otherwise normal colon may also show congestion of this area without or with minimal microscopic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…One possible explanation for the discrepancy between gene expression and pathology is that ceca exhibited discontinuous inflammation that was misrepresented in our assays. Discontinuous inflammation in the appendiceal orifice is often noted in IBD patients, but its presence does not correlate with clinical activity (13). Another explanation for the mismatch between IFN-␥ and IBD is that eventual suppression of histopathology may temporally lag behind suppression of cytokine transcriptional levels (i.e., taking 12 weeks instead of 8 weeks after infection).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the discrepancy between gene expression and pathology is that ceca exhibited discontinuous inflammation that was misrepresented in our assays. Discontinuous inflammation in the appendiceal orifice is often noted in IBD patients, but its presence does not correlate with clinical activity (13). Another explanation for the mismatch between IFN-␥ and IBD is that eventual suppression of histopathology may temporally lag behind suppression of cytokine transcriptional levels (i.e., taking 12 weeks instead of 8 weeks after infection).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, physicians have given more attention to AOI. After 1990, several endoscopic studies reported the incidence of AOI in UC patients, which ranged from 7.9% to 27.4% of all UC patients (5,(15)(16)(17) and from 9.4% to 75% in patients with only distal UC (12,(18)(19)(20). In the present study, we noted that the AOI + rate in UC was 26.2%, and this rate did not differ between patients with proctitis, left-sided colitis, and extensive colitis.…”
Section: Discussionmentioning
confidence: 99%
“…However some previous reports have suggested that appendiceal orifice inflammation (AOI) may occur as a skipped lesion in UC. 1,2 Wilson's disease is a rare genetic disorder of copper metabolism. One adult case report of UC complicating Wilson's disease has appeared, and suggested a possible association of UC with Wilson's disease.…”
Section: Introductionmentioning
confidence: 99%